2018
DOI: 10.1080/08995605.2018.1425063
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical olfactory function in combat Veterans: The role of PTSD and odor factors

Abstract: Stress- and trauma-related disorders, including posttraumatic stress disorder (PTSD), are characterized by an increased sensitivity to threat cues. Given that threat detection is a critical function of olfaction and that combat trauma is commonly associated with burning odors, we sought a better understanding of general olfactory function as well as response to specific trauma-related (i.e. burning) odors in combat-related PTSD. Trauma-exposed combat veterans with ( = 22) and without ( = 25) PTSD were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 69 publications
2
14
0
Order By: Relevance
“…Apart from the well-known neurological findings including sensory and motor deficits [ 6 ], some symptoms that we found, such as impairment of the senses (hearing, smell, taste), headache, vertigo, epilepsy and psychiatric symptoms, are rarely described in literature [ 31 , 38 ] and are often overlooked when treating patients with polytrauma. These should be actively screened for in patients with war injuries.…”
Section: Discussionmentioning
confidence: 90%
“…Apart from the well-known neurological findings including sensory and motor deficits [ 6 ], some symptoms that we found, such as impairment of the senses (hearing, smell, taste), headache, vertigo, epilepsy and psychiatric symptoms, are rarely described in literature [ 31 , 38 ] and are often overlooked when treating patients with polytrauma. These should be actively screened for in patients with war injuries.…”
Section: Discussionmentioning
confidence: 90%
“…Individuals with neurotic personality tendencies have been found to be both more susceptible to odor sensitization [92,93], and the development of PTSD [94]. The findings of Cortese et al [95] and Wilkerson et al [96] discussed in Section 6.1 also indicate that increased sensitivity to threat-relevant odors occurs in PTSD. Therefore, when using an odor habituation paradigm, it is important to monitor PTSD patients for odor sensitization to prevent maladaptive effects from arising.…”
Section: Inducing Adaptation and Habituation To Potential Trauma Odorsmentioning
confidence: 95%
“…Another important consideration for the use of OVR in PTSD therapy is that the condition of PTSD itself appears to alter odor processing. In several studies, Cortese and colleagues [95,96] found that veterans with PTSD exhibited elevated sensitivity to threatrelated odors (e.g., burning rubber, burning hair, diesel fuel, and gunpowder) as measured both by self-reported and objective odor testing. However, sensitivity to odors that were not associated with trauma were reduced in PTSD patients, and grey matter volume in both piriform and orbitofrontal areas (primary and secondary olfactory cortex) was also found to be diminished [95,96].…”
Section: Odor Perception Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study observed significant reductions of olfactory bulb volume and olfactory function in women with a history of CM (37). Moreover, olfactory dysfunctions and altered processing of non-social olfactory threat cues have been observed in individuals with posttraumatic stress disorder (PTSD) (38)(39)(40). However, whether CM modulates the processing of social olfactory cues remains unclear.…”
Section: Introductionmentioning
confidence: 99%